Quel pouvoir des sites Internet d’information concernant l’EZLN sur la sphère politique mexicaine et l’opinion publique internationale ? - Nathalie Blasco (Amnis)
This study seeks to analyse the influence of websites upon the Mexican political sphere and international public opinion with respect to the EZLN. Such a spread of information concerning the Neo-Zapatista mouvement and the personality of its charismatic leader, Sub-Commander Marcos, are probably the cause of the national and international success. The « Walk for Indigenous Dignity » has succeeded thanks to the media. The solidarity felt towards the EZLN by all those world-wide fighting for social justice and cultural diversity in resistence to the New World Order is also a consequence thereof. The message given out by Chiapaneca rebellion has reached today the protesters and Utopians world-wide because it has been relayed by the « New Generation » media. And by the same means the success obtained by the Neo-Zapatista mouvement on a strictly national level is most certainly at the root of the fear and stupor that have struck the Mexican leaders and of the upheaval caused in the highest political circles of the country. This explains why it is possible to talk about real influence and, to a certain extent, power.